О теоремах Еругина и Флокэ - Ляпунова для счетных систем разностных уравнений - Теплинский, Ю.В.; Теплинский, А.Ю. (Український математичний журнал, 1996)
For linear difference equations in the space of bounded number sequences, we prove an analog of the Erugin theorem on reducibility and present sufficient conditions for the reducibility of countable linear systems of difference equations with periodic coefficients. Для лінійних різницевих рівнянь у просторі обмежених числових послідовностей доведено аналог теореми Єругіна про звідність. Наведено достатні умови звідності зчисленних лінійних систем різницевих рівнянь з періодичними коефіцієнтами.